Al-qiyqm al-Islamiyyah and its impact on Muslim communities’ stability - Ahmed Mohamed, Ismaiel Hassanein; Idrus, Faizah; Mohammed Rawash, Fouad Mahmoud (2016)
Al-Qiyam is an Arabic term, means Values. The term: Qiyam is a plural of Qimah which means value. It addresses every aspect of a Muslim’s life, from greetings to international relations. It is universal in its scope and in its applicability. The distinction between human beings and other creatures is that human behaviours are controlled or limited by some ethical values (qiyam) which purify his soul. These qiyam are reliable benchmarks for the individual and societies’ behaviours, especially those who are practice Islamic ethics. Thus, the authorities handling educational institution and training centers are bound to teach the Islamic Qiyam to motivate tolerance, justice and equity among the Muslims. Thus,The objective of this paper is to explore the role of Islamic qiyam in guarding human behaviours, its implications on consolidation of unity among Muslim societies with diverse culture, and participation of educational institutions in instilling these qiyam among individuals, which eventually leads to the development of Muslim Nations; educationally, culturally, scientifically, economically and politically. The paper is based on a descriptive and analytical method, since it describes the qiyam suggested by the Holy Qur’an and the Sunnah, and to analyse the prevailing ethical problems among the Muslims, and how it could be resolved. The paper is intended to identify the most important values (qiyam) to be taught by various educational or training institutions in Islamic countries to serve as a comprehensive unifying framework for the Muslim Ummah.